Estado, tecnologia e sociedade: a política nacional de informática (Brasil, 1983-1984) - Santos, Marcos Moreira dos (2003)
The work deals with the institutionalization process of the National Informatics Policy, through the creation of a specific law, Law 7.232 / 84. debated in the National Congress between 1983 and 1984. Through this analysis, we sought to highlight the role of the State, already at the end of the Brazilian military dictatorship, as well as the participation of the various political and economic groups that manifested themselves in this process. In this study, it was also sought to apprehend a meaning of technology expressed by the interests and actions undertaken by the various agents involved, as well as, through some bibliographical references, to formulate a problem that allows reflecting on the relationship between State, technology and society in the recent history of the Brazil.